The Relationship of the Iqra Method to the Quran Reading Ability of Students at TPQ Nur Akbar, Kampung Sawah, Lubuk Basung - Indah Afri Lestari; Jamaris Jamaris (Universitas Negeri Padang, 2023)
The background of this research is the low value of the results of the ability to read the Koran for students in the Nur Akbar Al-Qur'an Education Park in Kampung Sawah, which is suspected to be due to the poor Iqra method used in carrying out the learning process. This study aims to describe the relationship between the Iqra method and the ability to read the Koran for students in the Nur Akbar Al-Qur'an Education Park, Sawah Village, Lubuk Basung District, Agam Regency. This study uses a quantitative approach with a correlational type. The population in this study is all students who are in groups into juz amma and Al-Qur'an. Sampling was done by using cluster random sampling. Data collection techniques using questionnaires as well as knowledge tests and skills tests. Data analysis technique using the rank order correlation formula. The results showed that the Iqra method that had been implemented was still classified as not good, the ability to read the Qur'an of the santri participants was still relatively low with a poor category, and there was a significant relationship between the Iqra method and the ability to read the Al-Qur'an of the santri participants in Nur Akbar Al-Qur'an Educational Park, Kampung Sawah, Lubuk Basung District, Agam Regency. This means that the use of the Iqra method can have an influence on improving the ability to read the Al-Qur’an. Suggestions in this study are that the ustad/ustadzah pay more attention to and also increase the application of the Iqra method in the implementation of learning carried out, it is hoped that the santri participants will be able to improve their ability to read the Al-Qur'an so that it can be even better, it is hoped that future researchers can deepen this research with a more complete variable. Keywords: iqra method, reading ability Al-Qur’an